High-fidelity, high-isotropic resolution diffusion imaging through gSlider acquisition with B(1)(+) & T(1) corrections and integrated ΔB(0)/Rx shim array - Liao, Congyu (Magn Reson Med, 2019)
PURPOSE: B(1)(+) and T(1) corrections and dynamic multi-coil shimming approaches were proposed to improve the fidelity of high isotropic resolution Generalized slice dithered enhanced resolution (gSlider) diffusion imaging. METHODS: An extended reconstruction incorporating B(1)(+) inhomogeneity and T(1) recovery information was developed to mitigate slab-boundary artifacts in short-TR gSlider acquisitions. Slab-by-slab dynamic B0 shimming using a multi-coil integrated ΔB(0)/Rx shim-array, and high in-plane acceleration (R(inplane)=4) achieved with virtual-coil GRAPPA were also incorporated into a 1 mm isotropic resolution gSlider acquisition/reconstruction framework to achieve a significant reduction in geometric distortion compared to single-shot EPI. RESULTS: The slab-boundary artifacts were alleviated by the proposed B(1)(+) and T(1) corrections compared to the standard gSlider reconstruction pipeline for short-TR acquisitions. Dynamic shimming provided >50% reduction in geometric distortion compared to conventional global 2(nd) order shimming. 1 mm isotropic resolution diffusion data show that the typically problematic temporal and frontal lobes of the brain can be imaged with high geometric fidelity using dynamic shimming. CONCLUSIONS: The proposed B(1)(+) and T(1) corrections and local-field control substantially improved the fidelity of high isotropic resolution diffusion imaging, with reduced slab-boundary artifacts and geometric distortion compared to conventional gSlider acquisition and reconstruction. This enabled high-fidelity whole-brain 1 mm isotropic diffusion imaging with 64 diffusion-directions in 20 minutes using a 3T clinical scanner.